Robert Neumann: Mit eigener Feder Untertitel Aufsätze. Briefe. Nachlassmaterialien - Stadler, Franz (Studien Verlag, 2013)
Robert Neumann (1897-1957, Austrian exiled author and Vicepresidet of the PEN International, was even a disputatious antifascist political writer. His essays, his letters and biograpical documents give a vivid portrait of the diversity of literary life in Germay and Austria (before 1933/after 1958) and of exile in England (1933-1958).